HATE CRIMES DI INDONESIA DALAM PERSPEKTIF PERBANDINGAN HUKUM - Wulandari, Widati (Veritas et Justitia, 2017)
This article discusses the deficiency of the Indonesian criminal law with regard to the criminalization of hate crimes. Taking into consideration the fact that Indonesia faces a high incidence of social conflict due to rising intolerance and discrimination targeting minority groups.  The combination of (racial-ethnic-religious) discrimination and hatred against minority groups in most cases results in various forms of common crimes which generally is known as hate crimes. Using a comparative law method, by and between Indonesian criminal law and the criminal law of other countries experiencing hate crimes, the author highlights options for eradicating hate crimes. One important finding is the tendency of a number of countries to perceive hatred or prejudice which motivate the perpetrator of hate crimes as aggravating factor and not to as as separate substantive offence.